Konsep Diri Akademik Mahasiswa Pascasarjana - Jusuf Blegur (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
This research reports the assessment of academic self-concept of the first semester postgraduate students from education, language and literature study program of State University of Surabaya. This research used descriptive qualitative approach. Respondents involved were 20 students (M=25.2500, SD = 2.46822) in which the determination of the respondents were done by the use of the total sampling. The data were collected using the Academic Self-Concept Questionnaire (ASCQ) developed by Woon C. Liu and Chee K. J. Wang in 2005 by involving the two dimensions that is of academic-conviction and academic effort. The result of the analysis indicated that 13 students (65%) responded to the research questioners in the value of 80-100 and 7 students (35%) responded to the questionnaire in the value of 60-80 whereas in the value of 40-60, and of 0-20 was not responded by the students (0%) in the research questionnaire. Finally, it can be inferred that students’ academic self-concept are very good (65%).